Manufacturing and Service Enterprise with Risks - Matsui, Masayuki (Springer, 2017)
This book presents a stochastic management approach for manufacturing and service enterprises with risks by a game/strategic view in order to show the goal and constraints on these enterprises and to provide a strategic/collaborative solution for management with risks in heterogeneity. The book focuses on the three manufacturing classes – continuous, point-wise and flexible stream types – under risks. These streams are first studied using the respective stochastic processes and are characterized and developed as a queueing/strategic control problem of look-ahead/buffer, selection/switchover, and arrangement/routings. Behaviors of some design/control variables are shown, and useful theories for design are established.